2019
DOI: 10.1103/physrevb.99.035162
|View full text |Cite
|
Sign up to set email alerts
|

Nonequilibrium dynamics of superconductivity in the attractive Hubbard model

Abstract: We present a framework of semiclassical superconductivity (SC) dynamics that properly includes effects of spatial fluctuations for the attractive Hubbard model. We consider both coherent and adiabatic limits. To model the coherent SC dynamics, we develop a real-space von Neumann equation based on the time-dependent Hartree-Fock-Bogoliubov theory. Applying our method to interaction quenches in the negative-U Hubbard model, we show that the relaxation of SC order at weak coupling is dominated by Landau-damping. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 64 publications
2
5
0
Order By: Relevance
“…The mode decays into a new state with spatially nonuniform order parameter. Numerical simulations performed for the attractive Fermi-Hubbard model [15,22] indicated that the mode is indeed dynamically unstable, which was consistent with the theoretical predictions.…”
Section: Introductionsupporting
confidence: 82%
“…The mode decays into a new state with spatially nonuniform order parameter. Numerical simulations performed for the attractive Fermi-Hubbard model [15,22] indicated that the mode is indeed dynamically unstable, which was consistent with the theoretical predictions.…”
Section: Introductionsupporting
confidence: 82%
“…V A) is the fact that practical sample sizes typically have linear dimension L ξ, where ξ = v F /π∆ is the coherence length. It can be shown that phase III is unstable in this case to the spontaneous generation of spatial fluctuations ("Cooper pair turbulence") [141,164]. The mechanism is parametric resonance.…”
Section: Fluctuation Phenomenamentioning
confidence: 95%
“…Here T ∆ is the characteristic period of ∆(t) oscillations (T ∆ is of the order of the inverse equilibrium gap ∆ 0f in our separable BCS models). Another limitation is the parametric instability of Phase III with respect to spontaneous eruptions of spatial inhomogeneities [89][90][91][92] . To avoid this instability, the system size has to be smaller than the superconducting coherence length.…”
Section: Discussionmentioning
confidence: 99%